Negative Emotion Expression and Lack of Social Support as Predictors of Adolescent Loneliness - Novak, Mateja; Abdulhussein, Omar (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to examine the predictive roles of negative emotion expression and perceived lack of social support in adolescent loneliness.Methods and Materials: A correlational descriptive design was used to investigate the relationships between the variables among 380 adolescents in Iraq. Participants were selected using stratified random sampling based on the Morgan and Krejcie table. Standardized self-report instruments were used to measure loneliness, negative emotion expression, and social support. Data were analyzed using SPSS-27, employing Pearson correlation coefficients to explore bivariate associations and multiple linear regression to assess the combined predictive power of the independent variables on loneliness. Assumptions for regression analysis—including normality, linearity, multicollinearity, and homoscedasticity—were checked and met prior to analysis.Findings: Descriptive statistics indicated moderate levels of loneliness (M = 47.38, SD = 10.27), high levels of negative emotion expression (M = 51.84, SD = 9.61), and low perceived social support (M = 28.42, SD = 6.83). Pearson correlations revealed that loneliness was positively associated with negative emotion expression (r = .47, p < .001) and negatively associated with social support (r = –.59, p < .001). Multiple regression analysis showed that both predictors significantly explained 45% of the variance in loneliness (R² = .45, F(2, 377) = 154.28, p < .001). Social support (β = –.48, p < .001) emerged as a stronger predictor than negative emotion expression (β = .31, p < .001).Conclusion: The findings highlight the critical role of both emotional and social factors in adolescent loneliness. Specifically, difficulties in expressing negative emotions and low perceived social support significantly contribute to elevated loneliness. Interventions aimed at enhancing emotion expression skills and strengthening social support networks may reduce loneliness and improve adolescent mental health.